Here you can ask questions and find or give answers to organizational, academic and other questions about studying computer science.

912 questions

1k answers

1.4k comments

441 users

0 votes

From paper 2019.02.13 Problem 2(a)

How did we go from (!b & c ^c ) to (b&c)?
Since and binds stronger than XOR.

I solved it as (!b & c ^c ) (distribution) -> (!b & c) ^ (!b&c) -> 0. T^T or F^F = 0

in * TF "Emb. Sys. and Rob." by (610 points)

1 Answer

0 votes
 
Best answer
    !b&c xor c 
    = (c ? !b&1 xor 1 : !b&0 xor 0)
    = (c ? !b xor 1 : 0 xor 0)
    = (c ? b : 0)
    = b&c
by (142k points)
selected by

Related questions

0 votes
1 answer
0 votes
1 answer
0 votes
1 answer
Imprint | Privacy Policy
...